Psychological Nature of Innovativeness in a Personality - O В Mikhailova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article provides a comparative theoretical analysis of creativeness, innovativeness and entrepreneurial spirit in a personality. Relying on this analysis, the author points out the principal differences in the concepts stated above and formulates the definition of innovativeness as of one of the factors generating innovative potential in a personality.